2020
DOI: 10.3390/pharmaceutics12050439
|View full text |Cite
|
Sign up to set email alerts
|

PLGA Nanoparticles for the Intraperitoneal Administration of CBD in the Treatment of Ovarian Cancer: In Vitro and In Ovo Assessment

Abstract: The intraperitoneal administration of chemotherapeutics has emerged as a potential route in ovarian cancer treatment. Nanoparticles as carriers for these agents could be interesting by increasing the retention of chemotherapeutics within the peritoneal cavity. Moreover, nanoparticles could be internalised by cancer cells and let the drug release near the biological target, which could increase the anticancer efficacy. Cannabidiol (CBD), the main nonpsychotropic cannabinoid, appears as a potential anticancer dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 69 publications
1
35
1
Order By: Relevance
“…Due to these limitations, nanoparticles loaded with CBD (CBD-NPs) at a ratio of 1:5 or 3% ( w / w ) have first been tested to treat ovarian cancer cells in vitro and for in vivo models. Compared to free CBD in organic solvents, CBD-NPs induce apoptosis and tumor growth inhibition at lower IC50 values [ 102 ]. CBD in lipid nanocarriers exhibits a high brain targeting ability by enhancing the passage across the blood-brain barrier in vitro and in ovo and, therefore, might provide a novel strategy to treat CNS tumors [ 103 ].…”
Section: Cbd and Cancermentioning
confidence: 99%
“…Due to these limitations, nanoparticles loaded with CBD (CBD-NPs) at a ratio of 1:5 or 3% ( w / w ) have first been tested to treat ovarian cancer cells in vitro and for in vivo models. Compared to free CBD in organic solvents, CBD-NPs induce apoptosis and tumor growth inhibition at lower IC50 values [ 102 ]. CBD in lipid nanocarriers exhibits a high brain targeting ability by enhancing the passage across the blood-brain barrier in vitro and in ovo and, therefore, might provide a novel strategy to treat CNS tumors [ 103 ].…”
Section: Cbd and Cancermentioning
confidence: 99%
“…Cannabinoid nanodelivery systems have been applied in vitro and in vivo to serve as therapeutic strategies. A number of studies are building nanoparticles for nanodelivery of cannabis, cannabinoids and ECS components as nanotherapeutics [6,[16][17][18][19][20][21][22][23][24][25][26]. They include strategies for creating cannabinoid delivery systems incorporating cannabinoid nanoconjugates in a multifunctional nanocarrier.…”
Section: Cannabinoid Nanodelivery Systemsmentioning
confidence: 99%
“…Some preliminary evidence suggests that OEA and its structural analogues may also have a beneficial effect on inhibiting ovarian cancer growth, but these data need to be confirmed in vivo [ 60 ]. There is little evidence that plant-derived (phyto)cannabinoids have any effect on ovarian biology or ovarian cancer development or progression, a concept that came from a study where SKOV-3-derived tumours were grown on the chorioallantoic membrane of fertilised chicken eggs [ 145 ], and then were treated with CBD-containing nanoparticles. The data indicated that CBD caused a 1.35- to 1.50-fold reduction in tumour size depending on the type of CBD formulation used [ 145 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is little evidence that plant-derived (phyto)cannabinoids have any effect on ovarian biology or ovarian cancer development or progression, a concept that came from a study where SKOV-3-derived tumours were grown on the chorioallantoic membrane of fertilised chicken eggs [ 145 ], and then were treated with CBD-containing nanoparticles. The data indicated that CBD caused a 1.35- to 1.50-fold reduction in tumour size depending on the type of CBD formulation used [ 145 ]. The authors indicated that these nanoparticle preparations might be useful in the treatment of peritoneal metastases of ovarian cancer, possibly with lower adverse drug effects [ 145 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation